Abdominal Wound Dehiscence after Caesarean Section. Issue 5756 (1st May 1971) - Mowat, James; Bonnar, John
Abstract : In a series of 2, 175 patients delivered by caesarean section a dehiscence of the abdominal wound occurred in 50. Wound dehiscence was eight times more common with a vertical incision than with a low transverse incision of the abdominal wall; with the vertical incision the incidence of partial and complete dehisence was 2·94% and with the low transverse incision no complete dehiscence occurred and the incidence of partial dehisence was 0·37%. The increased use of the low transverse incision would greatly reduce the serious complication of wound dehiscence after caesarean section.